Content validity of Scoliosis Research Society questionnaire-22 revised (SRS-22r) for adolescents with idiopathic scoliosis: protocol for a qualitative study exploring patient’s and practitioner’s perspectives - Alison B Rushton; Nicola R Heneghan; Deborah Falla; Emily Russell; Samia Alamrani; Adrian Gardner (BMJ Open)
Introduction Content validity is the most important measurement property for any patient-reported outcome measure (PROM). It being the extent that the PROM measures important concepts that are relevant to the population of interest. Adolescent with idiopathic scoliosis (AIS) is the most common spinal deformity in paediatric populations, with the Scoliosis Research Society questionnaire-22 revised (SRS-22r) a commonly used PROMof quality of life. In the absence of existing evidence, a content validity study for SRS-22r is needed to confirm its suitability for AIS. Thus, this study aims to investigate the content validity of SRS-22r for AIS. A secondary aim is to explore healthcare professional (HCP) perspectives of the barriers and facilitators to using outcome measures in AIS.Methods and analysis Qualitative study reported according to COnsolidated criteria for Reporting Qualitative Studies. A purposive sample of AIS (n=10–15, Cobb angle >25°, aged 10–18 years) will be recruited for online semi-structured interviews. A convenience sample (n=10–12) of HCP with clinical and/or research experience in AIS will be recruited for a focus group discussion. Topic guides and age-relevant documents are informed by existing evidence and developed using a framework of concept elicitation and cognitive debriefing. Audio-recordings will be transcribed verbatim, coded, analysed and synthesised using interpretive phenomenology analysis. Themes that generated from the analysis will be used as codes that will then be mapped to the SRS-22r contents.Ethics and dissemination The Health Research Authority and Health and Care Research Wales approval have been granted (IRAS 289888). Study findings will be disseminated through publications in peer-reviewed journals and conference presentations.